Effects of a Novel Magnesium Complex on Metabolic and Cognitive Functions and the Expression of Synapse-Associated Proteins in Rats Fed a High-Fat Diet - Orhan, Cemal; Tuzcu, Mehmet; Defo, Patrick Brice Deeh; Şahin, Nurhan; Ojalvo, Sara Perez; Sylla, Sarah; Şahin, Kazım (Springernature, 2022)
This study was conducted to compare the effects of a novel form of magnesium, Mg picolinate (MgPic), to magnesium oxide (MgO) on metabolic and cognitive functions and the expression of genes associated with these functions in rats fed a high-fat diet (HFD). Forty-two Wistar rats were divided into six groups: control, MgO, MgPic, HFD, HFD + MgO, and HFD + MgPic. Mg was supplemented at 500 mg of elemental Mg/kg diet for 8 weeks. MgPic and MgO supplementation decreased visceral fat, serum glucose, insulin, leptin, TC, TG, FFA, testosterone, FSH, LH, SHBG, IGF-1, and MDA levels, but increased brain SOD, CAT, and GSH-Px activities in HFD rats. Inflammation and cognitive-related markers (presynaptic synapsin PSD95, postsynaptic PSD93, postsynaptic GluR1, and GluR2) were improved in HFD rats administered Mg, with more significant effects seen in the MgPic group. MgPic also decreased brain NF-kappa B but elevated brain Nrf2 levels, compared with the HFD group. The phosphorylation levels of Akt (Thr308), Akt (Ser473), PI3K try 458/199, and Ser9-GSK-3 in the brain were improved after Mg treatment in HFD rats, with more potent effects seen from MgPic supplementation. MgPic has a higher bioavailability and is more effective in improving metabolic parameters and enhancing memory than MgO. The pro-cognitive effects of MgO and MgPic could be mediated via modulation of the AMPA-type glutamate receptor and activation of the PI3K-Akt-GSK-3 beta signaling pathway. These findings further support the use of MgPic in the management of metabolic and cognitive disorders.
Keywords: Magnesium picolinate; Magnesium oxide; Metabolism; Cognitive functions; High-fat diet